STRATEGI KOMUNIKASI BADAN PERTANAHAN NASIONAL MELALUI PROGRAM LARASITA DALAM MEMBERIKAN LAYANAN PUBLIK TERHADAP MASYARAKAT KABUPATEN SIJUNJUNG - Gilang Fijar Prasasty Utama; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Larasita is a People Service for Land Certification. This service has a strategy to pick up the ball that provides convenience to the community who do data collection and land measurement to be certified. So, people do not need to bother to register at the Badan Pertanahan Nasional office a long distance. With this Larasita Program, Sijunjung district with geographical location far and difficult to reach in the management of land becomes easier. The problem raised in this research is how communication strategy of Larasita Program in giving public service to society of Sijunjung Regency.This research used descriptive qualitative method, while the object of the research is Larasita Program at the Badan Pertanahan Nasional of Sijunjung Regency and research subjects including employees who are members of the Larasita team and also the community. Data collection techniques used are interviews, observation, and documentation.The results found First, the public audiences of public Larasita programs are far and unreached. Second, the message given in the form of informative messages and persuasion that invites the people to do data collection and making land certificates. Third, brochures, banners and radio are the media used by the Badan Pertanahan Nasional of Sijunjung Regency. Fourth, communicators come from Larasita team appointed by Decision, supported by Walinagari and local custom leaders who are more aware of the community criteria where the Larasita Program is held.Keyword : Larasita Program, Sijunjung, Land Certification